2005
DOI: 10.1016/j.yqres.2005.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate and river flooding on the hydro-ecology of a floodplain basin, Peace-Athabasca Delta, Canada since A.D. 1700

Abstract: Multi-proxy paleolimnological analyses on lake sediment cores from "Spruce Island Lake" (58° 50.82′ N, 111° 28.84′ W), a perched basin in the northern Peace sector of the Peace-Athabasca Delta (PAD), Canada, give insights into the relative roles of flow regulation of the Peace River and climatic variability on the basin hydro-ecology. Results indicate substantial variability in basin hydro-ecology over the past 300 years ranging from seasonal to periodic desiccation in the 1700s to markedly wetter conditions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
56
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 33 publications
5
56
0
Order By: Relevance
“…To supplement discharge data from the sparse river gauge network, multi-proxy paleolimnological studies of lake sediment records have been conducted in the PAD to investigate long-term variability in flood frequency. These studies aimed to tease apart the effects of multiple stressors on the hydrological regime of northern rivers, and to provide context within which to evaluate causes of contemporary hydrological change (Wolfe et al, 2005;2008a;b). Results have revealed that lakes perched above the river system may persist for decades in the absence of spring flooding (Wolfe et al, 2005), while others may dry up within a decade following a flood event (Peters et al, 2006a;Jaques, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To supplement discharge data from the sparse river gauge network, multi-proxy paleolimnological studies of lake sediment records have been conducted in the PAD to investigate long-term variability in flood frequency. These studies aimed to tease apart the effects of multiple stressors on the hydrological regime of northern rivers, and to provide context within which to evaluate causes of contemporary hydrological change (Wolfe et al, 2005;2008a;b). Results have revealed that lakes perched above the river system may persist for decades in the absence of spring flooding (Wolfe et al, 2005), while others may dry up within a decade following a flood event (Peters et al, 2006a;Jaques, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…These studies aimed to tease apart the effects of multiple stressors on the hydrological regime of northern rivers, and to provide context within which to evaluate causes of contemporary hydrological change (Wolfe et al, 2005;2008a;b). Results have revealed that lakes perched above the river system may persist for decades in the absence of spring flooding (Wolfe et al, 2005), while others may dry up within a decade following a flood event (Peters et al, 2006a;Jaques, 1989). Additionally, there have been oscillating multi-decadal periods of both high and low flood frequency over the last several hundred years, suggesting marked natural variability in flood recurrence intervals (Wolfe et al, 2006;2008a).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of lengthy hydrometric time series, a number of studies have used indirect proxy methods to extend the record of ice-jam flood activity in the PAD (Thomson, 1993;Peterson, 1995;Timoney et al, 1997;Timoney, 2002;Wolfe et al, 2005;. One approach involved historical documents, local knowledge and hydrometric data to develop a lengthy chronology of ice-jam floods along the lower Peace River (Thomson, 1993;Peterson, 1995;Timoney et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The compilation of information indicates 28 ice-jam floods ranging in magnitude from moderate to major occurred along the lower Peace River between 1826 and 2000, which translates to a 16% probability of recurrence in any given year (Timoney et al, 1997;Timoney, 2002). More recently, Wolfe et al (2005; used lake sediment cores to reconstruct water levels in perched basins as a proxy for ice-jam flooding. From high-resolution records extending back 300 years, Wolfe et al (2005; interpreted a highly variable flood chronology with several multi-decadal periods of low water levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation